2002
DOI: 10.1152/ajpgi.00269.2001
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D-inducible calcium transport and gene expression in three Caco-2 cell lines

Abstract: The parental cell line (P) of Caco-2 cells and two clones, BBe and TC7, were studied at 11 days postconfluence to test the facilitated diffusion model of vitamin D-mediated intestinal calcium absorption (CaTx). Nuclear vitamin D receptor (nVDR) and calbindin D 9k (CaBP) were measured by Western blot; 1,25-hydroxyvitamin D 3 24-hydroxylase (CYP24), CaBP, plasma membrane Ca-ATPase (PMCA), and Ca transport channel (CaT1) mRNA levels were examined by RT-PCR; and net apical-to-basolateral CaTx was examined after tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(89 citation statements)
references
References 38 publications
4
85
0
Order By: Relevance
“…The reduced renal TRPV5 expression and accompanied hypocalcemia were completely restored after 1,25(OH) 2 D 3 supplementation ). Similar results were obtained using different animal models and cell lines, including VDR and 1α-OHase knockout mice and the human intestinal cell line Caco-2, confirming the vitamin D-dependent regulation of TRPV5 and TRPV6 (Fleet et al 2002;Hoenderop et al 2002a;van Abel et al 2003;van Cromphaut et al 2001;Weber et al 2001;Wood et al 2001). Together these findings indicate that the expression of TRPV5 and TRPV6 is indeed controlled by 1,25(OH) 2 D 3 .…”
Section: Vitamin Dsupporting
confidence: 76%
See 1 more Smart Citation
“…The reduced renal TRPV5 expression and accompanied hypocalcemia were completely restored after 1,25(OH) 2 D 3 supplementation ). Similar results were obtained using different animal models and cell lines, including VDR and 1α-OHase knockout mice and the human intestinal cell line Caco-2, confirming the vitamin D-dependent regulation of TRPV5 and TRPV6 (Fleet et al 2002;Hoenderop et al 2002a;van Abel et al 2003;van Cromphaut et al 2001;Weber et al 2001;Wood et al 2001). Together these findings indicate that the expression of TRPV5 and TRPV6 is indeed controlled by 1,25(OH) 2 D 3 .…”
Section: Vitamin Dsupporting
confidence: 76%
“…VDR presence was demonstrated in prostate epithelial cells and vitamin D analogues were shown to inhibit the growth of primary cultures of human prostate tissue and cancer cell lines (Miller et al 1992;Peehl et al 1994;Zhao et al 2000). As discussed previously, the positive regulation of TRPV6 by 1,25(OH) 2 D 3 and several analogues has been clearly established (Fleet et al 2002;Weber et al 2001;Wood et al 2001). Apoptosis is induced by either depleting the cell or by overloading the cell with Ca 2+ (Haverstick et al 2000;Nicotera and Orrenius 1998;Rabinovitch et al 2001).…”
Section: Prostate Cancermentioning
confidence: 94%
“…In contrast we did not observe an increase in endogenous VDR protein abundance in parental Caco-2 cells. In addition, Figure 1B shows that ligand does not significantly alter the proportion of endogenous VDR in the nuclear extracts (1.2±0.2 after vitamin D treatment vs. 1.0±0.16 arbitrary units for control, P=0.4299, n=9) or in the whole cell extracts (P=0.9768, n=9) from Caco-2 cells, even though we have previously shown that this dose can activate CYP24 and TRPV6 mRNA accumulation in Caco-2 cells [Fleet et al, 2002]. …”
mentioning
confidence: 76%
“…NIH-PA Author Manuscript NIH-PA Author Manuscript of critical proteins: calbindin D 9k (CaBPD9k), the transient receptor vanelloid family member 6 (TRPV6), and the plasma membrane calcium ATPase 1b (PMCA1b) [Fleet et al, 2002;Song et al, 2003b;Fleet, 2006].…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation